Iron removal from underground water using coconut shell activated carbon filter - Muhamad, Mimi Suliza; Mohamad Roslan, Nor Atiqa; A.Rahman, Noor Khazanah; N.M., Sunar; R., Ali; Hamid, H. A.; Hamidon, N.; Harun, H. (Penerbit Uthm, 2018)
Raw water supplies are based on surface and groundwater sources all over the world. It is important to control the groundwater pollution in maintaining sustainable water sources. The common problem of groundwater sources is the high concentration of iron (Fe). These high concentration of iron results in metallic taste of water, effect color, health and cause environmental problem. Therefore, Ministry of Health Malaysia has set the standard quality control for iron in raw and drinking water to be 1.0 mg/L and 0.3 mg/L, respectively.